2014
DOI: 10.2478/johr-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evaluation of Germinability of Primed China Aster (Callistephus Chinensis Ness.) Seeds with Physiological and Biochemical Markers

Abstract: The correlation between the sowing value of primed China aster seeds represented by germination percentage (GP), mean germination time (MGT), germination uniformity expressed as the time between 25% and 75% of germinated seeds (T75-25) and some selected physiological characteristics - total activity of dehydrogenases (TAD), activity of catalase (AC), activity of cell cycle (ACC) and electrolyte leakage (EL) has been analysed in order to find useful markers of biological quality of seeds. To achieve this object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…According to Romanowska-Duda et al [79], measurements of the maximum potential quantum efficiency of PSII are useful in evaluations of the physiological activity of plants and can be recommended as markers of plant development. Similar observations were made by Badek et al [104,105] in a study of tomatoes and China asters and by Romanowska-Duda et al [106] who reported on the stimulatory effect of sewage sludge on the biomass yield of energy crops.…”
Section: Discussionsupporting
confidence: 85%
“…According to Romanowska-Duda et al [79], measurements of the maximum potential quantum efficiency of PSII are useful in evaluations of the physiological activity of plants and can be recommended as markers of plant development. Similar observations were made by Badek et al [104,105] in a study of tomatoes and China asters and by Romanowska-Duda et al [106] who reported on the stimulatory effect of sewage sludge on the biomass yield of energy crops.…”
Section: Discussionsupporting
confidence: 85%
“…The tests used to assess plant physiological activity are commonly recognized as useful markers of metabolic activity and plant responses to external stimuli (Badek et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In the performed research, the used maximal PSII efficiency measurements were comparable to activity of several enzymes (acid and alkaline phosphatase, RNase, dehydrogenase), index of chlorophyll content and gas exchange in leaves (net photosynthesis, transpiration, stomatal conductance and intercellular CO 2 concentration), which were useful in assessment of physiological activity in plants and were recommended to be a markers of plant development. It was shown in research on China aster and tomato (Badek et al, 2014, 2016) and in studies showing stimulatory impact of algae on Virginia fanpetals, corn and willow growth and biostimulants on apple seed germination (Grzesik et al, 2009; Grzesik and Romanowska-Duda, 2014, 2015; Grzesik et al, 2015; Grzesik et al, 2017a,b) and sewage sludge on energy plants biomass yield (Romanowska-Duda et al, 2010). It is believed that maximum PSII efficiency measurement can be used to monitor parameters that depend on the content and activity of chlorophyll, and thus it can be an indicator of plant growth, gas exchange, activity of certain enzymes, biomass yield and the amounts of elements which depends on the functioning photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%